An analysis on the factors affecting success of Results Based Personnel Performance System in Local Authorities in Zimbabwe.: a case study of Hurungwe Rural District Council. - Jembere, Courage (Midlands State University, 2020)
The study ought to analyse factors affecting success of Results Based Personnel Performance System (RBPPS) at Hurungwe Rural District Council (HRDC). The purpose of the study was to investigate and examine the main factors that impacted on the success of Results Based Personnel Performance System. Over the past decade Integrated Results Based Management (IRBM) has been adopted by the Zimbabwean government and public organisation to improve the implementation of national programmes based on oriented results. Results Based Personnel Performance System as a component of Integrated Results Based Management was adopted in 2005 with the expectation that there would be employees’ performance improvement in the public service. However the results had not been realizes as expected. Therefore the study sought to understand and analyse factors affecting success of Results Based Personnel Performance System in Zimbabwe local authorities using Hurungwe Rural District Council (HRDC) as a case study. Analyses of these factors could help the government and local authorities to identify strategies to improve the system and enhance employees’ performance. The study can also provide insight into the formulation of future initiative for implementation of other national policies. It is expected that this study will contribute towards providing Hurungwe Rural District Council and other local authorities, with recommendation and suggestions and strategies on how to improve the performance of their employees and to make them meet their set targets and objectives. The study used both primary and secondary data. The secondary data was obtained through study of relevant literature while primary data was obtained through questionnaires and interviews of the targeted employees at Hurungwe Rural District Council. Questionnaires were given to 40 Hurungwe Rural District Council employees and interviews were done. Content analysis was employed to identify themes. The findings emerged from the research indicated that unavailability of resources, lack of training and complexity of the system were the major factors affecting success of Results Based Personnel Performance System at Hurungwe Rural District Council. The main conclusion drawn from this study is that employees at Hurungwe Rural District Council were implementing Results Based Personnel Performance without the requisite knowledge of the system and there were not committed to it. The study argues that for Results Based Personnel Performance System to be a success at Hurungwe Rural District Council, employees should be committed to the system and embraces it. The managerial and non-managerial employees should receive service training on Results Based Personnel Performance System in order to understand the concepts of the system.